The use of magnetic resonance for diagnosis of multiple sclerosis (Research, Society and Development, 2020)
Multiple sclerosis (MS) is a type of neurological disease commonly diagnosed in young adult patients, with often unknown causes that can impact the quality of life of the affected person. The objective of this study is to present the peculiarities and applications of imaging diagnostic tests, more specifically magnetic resonance imaging in the diagnosis of multiple sclerosis through a literature review. The present work is a research proposal outlined and based on literature review studies for an integrative review. The result has been that magnetic resonance imaging, due to its high resolution images, has played an increasingly unique role in the diagnosis and treatment of multiple sclerosis patients, enabling the detection of small lesions. It is concluded that MRI can be considered an important resource to assist in the diagnosis of multiple sclerosis due to its relationships between the combinations of different types of pulse sequences and protocols, which make it possible to visualize the lesions, confirm the picture of MS and exclude the supposed alternative diagnoses that are similar.